ANALISIS KORELASI PERILAKU HEDONIC SHOPPING MOTIVATION, PRICE DISCOUNT DAN PEMBAYARAN ELEKTRONIK DI TOKO ONLINE SHOPEE TERHADAP PERILAKU IMPULSE BUYING - Miswan Gumanti; Bernadhita Herindri S. Utami (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
The stimulus factor of consumer by impulse buying behavior which is hedonic shopping motivation, price discount and ease of transaction by electronic payment. This research purpose to analyze the effects hedonic shopping motivation, price discount and electronic payment towards impulse buying behavior. Henceforth, by examining t-test was shown significant influencing hedonic shopping motivation and price discount were on impulse buying. Furthermore, electronic payment was unsignificant influencing towards impulse buying. However, the f-test result was significant effect by hedonic shopping motivation, price discount and electronic payment were on impulse buying.